Collective action towards a greener order of worth: protecting a common cultural and natural heritage - Jakob, Fabien (Technium Social Sciences Journal, 2022)
Built on Boltanski and Thévenot’s theory of justification, this study analyses a controversy that emerges during the revision of Greater Quebec City region land use planning schema that sparks public debate on the legitimacy of dezoning periuban agricultural lands. It highlights the capacities of stakeholders to develop robust justifications that aim to raise awareness of a natural and cultural heritage in all its manifestations in order to have it protected. It also demonstrates the role of meta-level ‘orders of worth’ as multiple modalities for agreement in accounting for the ways in which different stakeholder groups try to resolve socio-cultural and ecological problems in developping green justifications out of a plurality of forms of agreement.